Evaluation of shoreline changes at the coastal area of Jeram, Selangor / Abraham Aldo - Aldo, Abraham (2024)
The coastal zone of Jeram, Malaysia, is undergoing dynamic changes that warrant a comprehensive investigation to understand the evolution of its shoreline over the period from 2015 to 2023. This research utilises high-resolution Sentinel-2A satellite imagery to assess and analyse the spatiotemporal variations in the coastal landscape, focusing on the interplay between natural processes and anthropogenic influences. The study employs advanced remote sensing techniques and geospatial analyses to quantify shoreline changes, identify erosion and accretion patterns, and assess the impact of human activities on the coastal dynamics. The methodology involves the acquisition and processing of Sentinel-2A imagery at regular intervals, allowing for a detailed examination of seasonal and annual variations. Image classification techniques are applied to delineate the land covers. The digitization was used to identify the shoreline changes from 2015 to 2023. Study findings showed significant change in the Jeram shoreline, with discernible accretion in the study area. Natural factors such as tidal patterns, sediment transport, and wave dynamics are considered in interpreting these changes. Moreover, the impact of anthropogenic activities, including urban development, coastal infrastructure, and land use changes, is evaluated to elucidate their contribution to the observed shoreline alterations. Additionally, the role of climate change in exacerbating these effects is explored, considering sea-level rise and increased storm intensity as potential contributing factors. The study also addresses the implications of shoreline changes on the local ecosystem, including impacts on biodiversity, habitat loss, and potential threats to coastal communities.